Influence of polymerization pressure and post-cure treatment on conversion degree and viscoelastic properties of polymer infiltrated ceramic network. (March 2021) - Pomès, Benjamin; Behin, Pascal; Jordan, Laurence; Legoff, Stéphane; Stoclet, Gregory; Richaud, Emmanuel; Nguyen, Jean-François
Abstract: This study aimed at determining an optimum polymerization pressure for Polymer Infiltrated Ceramic Network (PICN) blocks by characterizing the conversion degree (DC) and the viscoelastic properties of experimental PICN blocks polymerized at 90 °C under various high pressures followed or not by post-cure treatment (PC). Near infrared analysis and dynamic mechanical analysis were used to characterize DC and viscoelastic properties of sixteen PICN: one control (thermo-cured) and fifteen experimental groups (one thermo-cured followed by PC and fourteen high pressure polymerized PICN, in the range of 50–350 MPa without and with PC). Conversion degree of high pressure polymerized PICN blocks without post curing displays an optimum between 100 and 150 MPa resulting in an improved E′ and Tg . Post curing induces a higher DC with a controversial effect on thermomechanical properties. The results suggested that 100–150 MPa without PC is an optimum polymerization parameter, resulting in PICN blocks with significantly better DC, Tg, E'. Highlights: Optimal pressure of experimental PICN is 100–150 MPa in the conditions of the study. Effect of post curing seemed to be a balance between a gain in DC and a loss due to polymer degradation. Viscoelastic properties of PICN could reduce stress at the interface dentin/dental restoration.